1993
DOI: 10.1007/bf00021816
|View full text |Cite
|
Sign up to set email alerts
|

Differential, temporal and spatial expression of genes involved in storage oil and oleosin accumulation in developing rapeseed embryos: implications for the role of oleosins and the mechanisms of oil-body formation

Abstract: The temporal and spatial expression of oleosin and delta 9-stearoyl-ACP desaturase genes and their products has been examined in developing embryos of rapeseed, Brassica napus L. var. Topas. Expression of oleosin and stearate desaturase genes was measured by in situ hybridisation at five different stages of development ranging from the torpedo stage to a mature-desiccating embryo. The temporal pattern of gene expression varied dramatically between the two classes of gene. Stearate desaturase gene expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 49 publications
7
36
0
Order By: Relevance
“…It has been speculated that oleosins stabilize oilbodies preventing coalescence of the lipid particles during seed dehydration (Cummins et al, 1993). Some authors have also suggested that oleosins prevent oilbodies from coalescing during seed imbibition and germination (Leprince et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that oleosins stabilize oilbodies preventing coalescence of the lipid particles during seed dehydration (Cummins et al, 1993). Some authors have also suggested that oleosins prevent oilbodies from coalescing during seed imbibition and germination (Leprince et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of oil-body proteins, particularly oleosin, has been extensively investigated via in vivo systems using transgenic techniques and in vitro systems using microsomal membranes for integration of translated proteins [107][108][109][110][111]. The signal segment for specific targeting of oleosin to oil bodies is apparently located within the protein itself since recombinant oleosins are able to target correctly oil bodies in different transgenic plants and yeasts [112][113][114].…”
Section: Targeting Of Integral Oil-body Proteinsmentioning
confidence: 99%
“…The oil accumulation of B. napus seeds usually starts around 3 weeks after flowering and peaks after another 3 weeks (Norton and Harris, 1975;Cummins et al, 1993;Eastmond and Rawsthorne, 2000). The seed oil content varies significantly among B. napus cultivars or under different growth environments.…”
mentioning
confidence: 99%